Proust est-il un philosophe ? - Fraisse, Luc (Studia Romanica Posnaniensia, 2015)
Different philosophers pondered on Proust’s novel, including those who formulated a subtle hypothesis that philosophical thought that emerged from the novel went beyond the passages of philosophical character that could be found in Proust’s work. It is difficult to determine precisely Proust’s approach towards the novel which he, alternately, favors or disdains. A hypothesis has been formulated that In Search of Lost Time shapes the fiction in the style of Shelling’s and Schopenhauer’s philosophy; it is pointed out that the novelist developed a kind of rivalry between him and his second cousin Bergson. Proust received a thorough education in philosophy yet philosophy is only present in his novel in an anecdotal form. The debate that he starts between idealism and philosophical realism in his prose takes the form of a discussion between symbolism and naturalism. The reconstruction of Proust’s philosophical culture leads to the observation that it is, without a doubt, significantly influenced in different ways by two philosophers: Leibniz and Kant. Still, the writer does not admit to being impacted by any particular thinker; therefore, his narrator’s line of thought is constantly changing in such a way that any school of philosophical thought that appears in the novel is present only for a short while.